The human development-economic growth nexus - Marques, Rodrigo Filipe do Carmo (2020)
The economies of oil-producing countries are known for their peculiarities. This study analyses the causal relationship between human development and economic growth in oil-producing countries. The model comprises variables such as gross domestic product, human development index, oil rents, exports of goods and services, the ratio of oil production to oil consumption and oil prices. The sample consists of 15 countries and a period from 1990 to 2016. The autoregressive distributed lag (ARDL) model was used to analyse the dynamic short- and long-run relationships between variables. The Driscoll-Kray estimator proved to be adequate to deal with the panel's characteristics. The results reinforce the importance that human development plays in economic growth both in the short and long run and support the hypothesis of a resource curse.